The Performance of Top R&D Investing Companies in the Stock Market - Michele Cincera; Raquel Ortega-Argilés; Pietro Moncada-Paternò-Castello (European Commission, Joint Research Centre (JRC), 2009)
Based on an original data set with information of a representative portfolio of among the largest 304 R&D investing companies over the 2003-2006 period, the overall analysis, except in a few cases, gives some robust evidence of a positive relationship between top R&D-investing companies and their performance in the stock markets as measured by the evolution of their market capitalisations' values. In terms of sectors, companies in the pharmaceuticals and biotechnology and software & computer services sectors in the UK and the chemicals sector in Germany appear to outperform the respective sectoral stock market indexes in which they operate. On the other hand some other sectors, such as technology hardware and equipment one in France, show an underperforming behaviour. Empirical findings from the econometric analysis suggest a positive impact of the firm's R&D intensity on its market capitalisation performance. Besides some data limitations which call for further investigations, R&D investment can without uncertainty be acknowledged as representing an important strategic element for companies' economic and financial performance, but is not the only one. To name a few of them, framework conditions in the economy, marketing activities and the level of market power of companies are only other important factors that have an impact on companies' performances which are also reflected on their stock markets values.
Keywords: G30; L60; O31; 330; top R&D firms; market capitalisation performance; R&D intensity; size of R&D investments